PENGARUH MARKETPLACE TERHADAP PENINGKATAN PENDAPATAN PADA UKM (STUDI PADA UKM DI DAERAH ISTIMEWA YOGYAKARTA) - Evi Rosalina Widyayanti (Universitas Ahmad Dahlan, 2019)
The role of technology is very strong to the changes of civilization today. The impact of technological progress also has an influence on the marketing strategy that must be carried out by SMEs. One of the strategy is by selling through a marketplace where this method is becoming a trend for customers. This research aims to find out how the influence of the sales strategy through an online store marketplace to increase income in SMEs (Small and Medium Enterprises) in Daerah Istimewa Yogyakarta (DIY). To answer the aim of the research, it was conducted the research by taking 100 sample of SME which lived in DIY. The method used to take sample is non-probability sampling method. It is taking sample by deciding special criteria to the SME in DIY. The data collecting technique is using questionnaire that has been tested of validity and reliability. The data analysis technique is using multiple linier regression analysis and the data processed with SPSS software version 17 for windows. Based on the results of the analysis, it can be seen that the Marketing Mix variable on sales of the online marketplace stores has a positive effect on increasing the income of SMEs, Human Resources variable on sales of the online marketplace stores has a negative effect on increasing the income of SMEs, Information Technology variable on sales of the online marketplace store has a significantly positive effect on increasing SME income, and also expedition variable has a positive influence on increasing SME income. The simultaneously variables or together, variable Marketing Mix, Human Resources, Information Technology and Expedition affect on sales of the online marketplace stores which ultimately affect on the increase of SME income. Marketing Mix Variables, Human Resources variables, Information Technology variables, and Expedition variables explain the effect on the online store marketplace sales toward increasing SME income.